Recombination between Homeologous Chromosomes in Lager Yeasts leads to Loss of Function of the Hybrid GPH1 Gene. - BOND, URSULA (My University, 2009)
Yeasts used in the production of lagers contain complex allopolyploid genomes, resulting from the fusion of two different yeast species closely related to Saccharomyces cerevisiae and Saccharomyces bayanus. Recombination between the homoeologous chromosomes has generated a number of hybrid chromosomes. These recombination events provide potential for adaptive evolution through the loss or gain of gene function. We have examined the genotypic and phenotypic effects of one of the conserved recombination events that occurred on chromosome XVI in the region of YPR159W and YPR160W. Our analysis shows that the recombination event occurred within the YPR160W gene, which encodes the enzyme glycogen phosphorylase and generates a hybrid gene that does not produce mature mRNA and is nonfunctional due to frameshifts in the coding region. The loss of function of the hybrid gene leads to glycogen levels similar to those found in haploid yeast strains. The implications for the control of glycogen levels in fermentative yeasts are discussed.
PUBLISHED
Keywords: Yeasts; Yeasts; Genes & Society